The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/cphc.201701108
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Interactions in Monolayer and Few‐Layer SnS/CH3NH3PbI3 Perovskite van der Waals Heterostructures and Their Effects on Electronic and Optical Properties

Abstract: A high light-absorption coefficient and long-range hot-carrier transport of hybrid organic-inorganic perovskites give huge potential to their composites in solar energy conversion and environmental protection. Understanding interfacial interactions and their effects are paramount for designing perovskite-based heterostructures with desirable properties. Herein, we systematically investigated the interfacial interactions in monolayer and few-layer SnS/CH NH PbI heterostructures and their effects on the electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…2f ]. 19 The photo-generated holes within the CH 3 NH 3 PbI 3 are transferred to the SnS due to type-II heterojunction, resulting in the improved overall performances.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2f ]. 19 The photo-generated holes within the CH 3 NH 3 PbI 3 are transferred to the SnS due to type-II heterojunction, resulting in the improved overall performances.…”
Section: Resultsmentioning
confidence: 99%
“…One can see that the photocurrent decreases from UV to visible range and responds even at 850 nm. 19 However, it has been predicted from the density functional theory that the band gap of the hybrid CH 3 NH 3 PbI 3 /SnS is reduced to NIR range, which in turn make it very suitable to design broadband photodetector. The present device may offer the possibility to design an advanced broad band photodetector over a large area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proved that theoretical simulation can offer powerful insight into the fundamental understanding of structures and properties of interfaces. DFT calculations conducted by Huang et al 43 indicated that staggered band alignment formed at the interface of SnS/MAPbI 3 is beneficial for electron–hole separation. Theoretical calculations of Chang et al 32 predicted that the MAPbI 3 /SnO 2 interface with PbI termination possesses more excellent and stable properties than those of MAPbI 3 /SnO 2 interfaces with other configurations and MAPbI 3 /TiO 2 interfaces, and their experimental observations of current density ( J sc ), open circuit voltage ( V oc ), fill factor (FF), and PCE verified their theoretical prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the perovskite-based solar cell with the efficiency of 23.2% is successfully fabricated by virtue of fluorine-terminated holetransport materials instead of common spiro-MeOTAD. 20 Simultaneously, the stability of the resultant device is dramatically enhanced because its initial performance still retained 95% after 500 h. So far, there are two major strategies of improving the performance of the PSCs, one is forming heterostructure by selecting a suitable coating layer such as SnS/MAPbI 3 , 21,22 which has been confirmed to have superior performance than the pure MAPbI 3 ; the other is through ion doping. First, the band gap can be effectively tuned by means of organic cation doping, although they almost have little contribution to the electronic states at the band-gap edges.…”
Section: ■ Introductionmentioning
confidence: 99%